The Meaning of Patience in Islamic Psychological Perspective: a Life Effort for Physical Disabilites - Hani, Lusia; Reza, Iredho Fani; Mansur, Abu (Journal of Islamic and Contemporary Psychology, 2021)
This study aims to find out how people with physical disabilities understand the meaning of patience in an effort to live life. Using qualitative research with a phenomenological research design. Sampling using purposive sampling technique, namely 6 subjects consisting of men and women with physical disabilities. Methods of data collection using interviews, observation and documentation. While the data analysis method uses an interactive model which consists of three stages, namely data condensation, data display and conclusions: drawing. The results of this study conclude that the meaning of patience for people with physical disabilities is trying to stay calm, not complaining and not doing bad things and not doing things that are forbidden by Allah SWT by surviving and struggling, limiting themselves, Refrain from people's ridicule and always be optimistic about life. The factors that affect patience in people with physical disabilities are religiosity and social support.